2006
DOI: 10.1111/j.1365-2222.2006.02565.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastro‐duodenal digestion products of the major peanut allergen Ara h 1 retain an allergenic potential

Abstract: Gastro-duodenal digestion fragments of Ara h 1 retain T cell stimulatory and IgE-binding and cross-linking properties of the intact protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 38 publications
9
77
0
Order By: Relevance
“…[10], [120], [121], [122] and [123] [124], [125], [126], [127], [128], [129] and [130] However, other studies at different shifting offsets, with different peptides sizes, or both revealed different sets of immunodominant sequential epitopes for the same allergens. [29], [124], [125], [126], [127], [130] and [131] Nevertheless, approaches to use these alleged immunodominant peptides for the risk assessment of life-threatening symptoms, as well as the prediction of persistence in food hypersensitivity, were apparently successful.…”
Section: Diagnosis Of Food Allergy With Synthetic Sequential Epitopesmentioning
confidence: 99%
“…[10], [120], [121], [122] and [123] [124], [125], [126], [127], [128], [129] and [130] However, other studies at different shifting offsets, with different peptides sizes, or both revealed different sets of immunodominant sequential epitopes for the same allergens. [29], [124], [125], [126], [127], [130] and [131] Nevertheless, approaches to use these alleged immunodominant peptides for the risk assessment of life-threatening symptoms, as well as the prediction of persistence in food hypersensitivity, were apparently successful.…”
Section: Diagnosis Of Food Allergy With Synthetic Sequential Epitopesmentioning
confidence: 99%
“…The protocol followed was derived from prior reports (19,20,21). Lyophilized powders of enzymes and comparator proteins (α-casein from bovine milk, β-lactoglobulin from bovine milk, trypsin inhibitor from Glycine max) as well as reagents were purchased from Sigma-Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…We evaluated the digestibility of colicin proteins in the human GI tract using treatments with simulated gastric and intestinal fluids (SGF and SIF, respectively). Sequential exposure studies using physiological enzyme-to-substrate ratios were conducted to mimic the natural human GI tract conditions (19)(20)(21). For these studies, the colicins were first exposed to either SGF without or with pepsin, at a pepsin-to-colicin ratio of 1:20 on a weight basis, followed by exposure of the resultant hydrolysate products to SIF supplemented with trypsin and chymotrypsin at a ratio of 1:4:400 (trypsin:chymotrypsin:colicin peptides, on a weight basis).…”
Section: Gastric and Intestinal Proteases Digest Plant-produced Colicmentioning
confidence: 99%
“…23,24 Ara h 1 is a readily digestible allergen, being digested to small peptide fragments by gastroduodenal digestion. 9,10 Even though Ara h 1 is a labile protein, Eiwegger et al 9 and Bøgh et al 10 showed that the digestion products of Ara h 1 retain allergenic potential, being able to sensitize as well as elicit allergic reactions. These studies indicated that aggregation of peptides may play a major role in maintaining allergenic activity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…11−13 However, while pepsin stability as a part of an allergenicity assessment would still seem reasonable for the purpose of safety evaluation of most food proteins, we now know that for some allergenic proteins, this approach would be misleading. The milk allergen β-casein (Bos d 8) 7,14,15 as well as the peanut allergen Ara h 1 9,10 have several times been shown to be easily digestible food allergens.…”
Section: ■ Introductionmentioning
confidence: 99%